Predictors of career aspiration of Malaysian returnees from European and non-European countries - Ismail, Maimunah; Yeop Kamaruddin, Noor Ainun; Umar Baki, Nordahlia; Mohd Rasdi, Roziah (2014)
This study aims to identify profiles and predictors of career aspiration of Malaysian returnees from European and non-European countries. This study, involving 226 returnees, was carried out in the industrialized areas of the Klang Valley, Johore Bharu and Penang, and the state of Sabah. Four theories were applied in the analysis, namely the Push-Pull Theory, the Human Capital Theory, the Social Cognitive Career Theory, and the Chaos Theory of Careers. Personal and environmental factors within the major groups of push and pull factors, as well as age and duration abroad served as the independent variables while career aspiration was the dependent variable. Most returnees from Europe came back from the United Kingdom while Australia, Saudi Arabia, Japan, Korea and the United States were the host countries outside of Europe. Accounting and finance (20.9%) was the leading professional sector for the European returnees, while medicine (18.9%) was the most common work sector among non-European returnees. A regression analysis showed the explanatory power of career aspiration for returnees from European countries was higher (33.9%) than that of returnees from non-European countries (30.0%). Push political and pull social factors were significant for the former group, whereas push social, pull personal and pull family factors were for the latter. Implications of these findings to global HRD are discussed.